Microplastics in mussels along the coastal waters of China. (July 2016) - Li, Jiana; Qu, Xiaoyun; Su, Lei; Zhang, Weiwei; Yang, Dongqi; Kolandhasamy, Prabhu; Li, Daoji; Shi, Huahong
Abstract: Microplastic has been confirmed as an emerging pollutant in marine environments. One of the primary environmental risks of microplastics is their bioavailability for aquatic organisms. Bivalves are of particular interest because their extensive filter-feeding activity exposes them directly to microplastics present in the water column. In the present study, we investigated microplastic pollution in mussels ( Mytilus edulis ) from 22 sites along 12, 400 mile coastlines of China in 2015. The number of total microplastics varied from 0.9 to 4.6 items/g and from 1.5 to 7.6 items/individual. M. edulis contained more microplastics (2.7 items/g) in wild groups than that (1.6 items/g) in farmed groups. The abundance of microplastics was 3.3 items/g in mussels from the areas with intensive human activities and significantly higher than that (1.6 items/g) with less human activities. The most common microplastics were fibers, followed by fragments. The proportion of microplastics less than 250 μm in size arranged from 17% to 79% of the total microplastics. Diatom was distinguished from microplastics in mussels for the first time using Scanning Electron Microscope. Our results suggested that the numbers of microplastic kept within a relatively narrow range in mussels and were closely related to the contamination of the environments. We proposed that mussels could be used as a potential bioindicator of microplastic pollution of the coastal environment. Graphical abstract: Highlights: Microplastics varied from 0.9 to 4.6 items/g in Mytilus edulis . M. edulis contained more microplastics in wild groups than farmed groups. The most common microplastics were fibers. Diatom was distinguished from microplastics in mussels. Mussels could be used as a potential bioindicator of microplastic. Abstract : Microplastics varied from 0.9 to 4.6 items/g in wild and farmed Mytilus edulis from 22 sites along the coastal waters of China.